Assessment of Serum Inflammatory Markers as Predictors of Left Ventricular Diastolic Dysfunction in Hypertensive Patients - Muhammad Zahid Ali Raza, Aamir Siddique, Shaoib Ahmed Zia, Tayyab Mohyuddin, Arslan Aslam Chahudhary, Faiza Altaf (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Left ventricular diastolic dysfunction (LVDD) is a common but underrecognized cardiac complication in hypertensive individuals and serves as an early precursor to heart failure with preserved ejection fraction (HFpEF). Inflammatory mechanisms are increasingly implicated in its pathogenesis, yet limited data exist on the predictive role of circulating biomarkers in resource-constrained settings. Objective: To evaluate the predictive significance of serum inflammatory biomarkers high-sensitivity C-reactive protein (hs-CRP), interleukin-6 (IL-6), tumor necrosis factor-alpha (TNF-α), and fibrinogen for the presence of LVDD in hypertensive patients. Methods: This cross-sectional clinical study was conducted from June 2022 to January 2023 at Aziz Bhatti Shaheed Teaching Hospital, Gujrat, and Chaudhary Pervaiz Elahi Institute of Cardiology, Wazirabad, Pakistan. A total of 100 hypertensive patients aged 40–75 years were enrolled through consecutive non-probability sampling. Detailed demographic and clinical data were collected. Diastolic function was assessed via transthoracic echocardiography in accordance with American Society of Echocardiography (ASE) guidelines. Fasting blood samples were analyzed for hs-CRP, IL-6, TNF-α, and fibrinogen. Statistical comparisons between patients with and without LVDD were performed using SPSS version 27. Results: LVDD was identified in 64% of patients. Those with LVDD exhibited significantly higher mean levels of hs-CRP (4.1 ± 1.3 mg/L), IL-6 (6.8 ± 2.5 pg/mL), TNF-α (7.9 ± 2.1 pg/mL), and fibrinogen (452 ± 87 mg/dL), compared to non-LVDD patients (2.3 ± 0.9 mg/L, 3.2 ± 1.4 pg/mL, 4.5 ± 1.8 pg/mL, and 341 ± 66 mg/dL respectively; p < 0.001 for all). Age, BMI, and duration of hypertension were also significantly associated with the presence of LVDD, whereas gender and smoking history were not. Conclusion: Serum inflammatory biomarkers are significantly elevated in hypertensive patients with LVDD, underscoring the contributory role of chronic inflammation in diastolic dysfunction. These biomarkers may serve as accessible and cost-effective tools for early identification and risk stratification of LVDD, particularly in clinical settings where echocardiographic resources are limited. Keywords: Hypertension, Left Ventricular Diastolic Dysfunction, Inflammatory Biomarkers, hs-CRP, Interleukin-6, TNF-α, Fibrinogen, Echocardiography, HFpEF